Association between Smoking and Health Outcomes in Postmenopausal Women Living with Multiple Sclerosis. (22nd April 2014) - Jawahar, Rachel; Oh, Unsong; Eaton, Charles; Wright, Nicole; Tindle, Hilary; Lapane, Kate L.
Abstract : Background . In multiple sclerosis (MS), symptom management and improved health-related quality of life (HrQOL) may be modified by smoking. Objective . To evaluate the extent to which smoking is associated with worsened health outcomes and HrQOL for postmenopausal women with MS. Methods . We identified 251 Women's Health Initiative Observational Study participants with a self-reported MS diagnosis. Using a linear model, we estimated changes from baseline to 3 years for activities of daily living, total metabolic equivalent tasks (MET) hours per week, mental and physical component scales (MCS, PCS) of the SF-36, and menopausal symptoms adjusting for years since menopause and other confounders. Results . Nine percent were current and 50% past smokers. Age at smoking initiation was associated with significant changes in MCS during menopause. PCS scores were unchanged. While women who had ever smoked experienced an increase in physical activity during menopause, the physical activity levels of women who never smoked declined. Residual confounding may explain this finding. Smoking was not associated with change in menopausal symptoms during the 3-year follow-up. Conclusion . Smoking was not associated with health outcomes among post-menopausal women with MS.